Late Cenozoic tectonic evolution of the southern segment of the Tan-Lu fault zone, Eastern China. (15th September 2019) - Jiang, Ren; Cao, Kai; Zeng, Jianwei; Liu, Kai; Li, Changbo; Wang, An; Yu, Junjie; Peng, Bo; Lao, Jinxiu; Zhao, Ling
Graphical abstract: Highlights: The Jiji-Wangji and Shanzuokou-Sihong faults had a normal sense in the Neogene. The Xinyi-Xindian and Qiaobeizhen-Suqian faults were the most active dextral faults. A kinematic change of the Tan-Lu fault occurred by the middle-late Pleistocene. Abstract: The knowledge of the geometry, kinematics, assemblage and evolution of the Tan-Lu fault zone in late Cenozoic times remains scarce, despite its importance to understanding regional geodynamics and relevant mineralization and seismicity. To address the above issues, we provide new results of morphotectonic analysis, geological mapping, boreholes, seismic reflection and geochronology in the southern Tan-Lu fault zone at Sihong, Jiangsu Province, Eastern China. Field mapping in line with drilling and seismic reflection data suggest that the east-dipping Jiji-Wangji fault (F4 ) and west-dipping Shanzuokou-Sihong fault (F1 ), as the boundaries of the Tan-Lu fault zone, have been likely reactivated in a normal sense since the middle Neogene, and continued by the early-middle Pleistocene. These two faults predominantly controlled a graben that was filled by fluvial deposits in the fault zone. Additionally, the east-dipping Xinyi-Xindian fault (F2 ) and west-dipping Mohe-Lingcheng fault (F3 ) within the Tan-Lu fault zone had similar kinematics but behaved less active during the same time interval. The assemblage of the faults F1 -F4 defined a horst-graben system in the Neogene-early Quaternary. During the late Pleistocene, intense deformation of the Tan-Lu fault zone concentrated on two splay faults, namely the fault F2 and Qiaobeizhen-Suqian fault (F5 ), while fault F4 likely ceased. These two active faults (F2 and F5 ) were interpreted as reverse dextral strike slip structures under a NE-oriented compressional stress field, in which the other two faults F1 and F3 changed the normal sense to reverse. The activities of faults F1 and F5 caused uplift of the Chonggang Hill and controlled sedimentary depocenters between these two faults as revealed by boreholes. Optically stimulated luminescence data place age control on the activities of the reactivated fault F2 between 105.6 ± 1.1 ka and 46.9 ± 5.9 ka and a newly developed fault F5 between 135.6 ± 10.6 ka to 23.96 ± 1.69 ka. Based on these results, we reconstructed the late Cenozoic tectonic evolution of the Tan-Lu fault zone, in which a dramatic kinematic shift probably occurred by the middle-late Pleistocene, possibly resulted from the far-field effect of the Indo-Asian convergence.